The Fundamental of Law Enforcement Authority in Marince Accidents with the Police in Indonesian Waters - Ni Made Rai Sukardi; I Wayan Parsa; Ni Nengah Adiyaryani; Sagung Putri M.E.Purwani (Formosa Journal of Science and Technology, 2024)
The sea is the boundary between a country and another country which is determined through extradition. On December 13, 1957 the government issued a statement known as the Djuanda Declaration with the intention of uniting the fragmented land areas so that the declaration would close the existence of the open sea between mainland islands by covering the problem of the ideal concept of regulating the authority to enforce maritime accident laws in indonesian territorial waters. The approach method in this research is normative juridical based on an analysis of the law. Then it is described in a descriptive-analytical description. The problem is investigated by describing/describing the condition of the subject/object of research, finding facts thoroughly, and systematically reviewing national regulations. Conclusion maritime law enforcement can cause potential friction between one institution and another. For this reason, this research provides a concept that maritime security and law enforcement institutions will be productive and effective-efficient if they are in accordance with Pancasila.